Geochemical characterisation of the late cretaceous coal and mudstones from gombe formation, gongola sub-basin, Northern Benue trough, Nigeria / Ayinla Habeeb Ayoola - Ayinla Habeeb, Ayoola (2018)
The discovery of proven coal reserve of about 4.5 million tons and recent exploration activities at the Maiganga coal mine uncover some missing gaps in the stratigraphy of the Upper Cretaceous Gombe Formation. Therefore, there is a need to further investigate this sequence, including the organic and inorganic facies variations and distributions of the coals, mudstones and sandy-shaly sediments in the Gombe Formation, Gongola Sub-basin, Northern Benue Trough of Northeastern Nigeria. Organic and inorganic geochemical methods were used to assess the organic matter source input, paleodepositional conditions, thermal maturity, kerogen type, hydrocarbon generation potential, tectonic setting and paleoclimatic condition of the analysed Maiganga and Yaya-Ngari samples. Field observations showed four coal seams interbedded with mudstones and shales deposited in coarsening upward sequence of a deltaic environment. Evaluation based on the source rock analyses (SRA) and organic petrography reveal that Maiganga sedimentary facies is dominated by terrestrial source input of Type III kerogen. This is supported by the biomarker study suggesting land plant origin (dominance of n-C27, n-C29 and n-C31) for the organic matter with minor lacustrine and marine influences, in Maiganga, that grades into predominantly mixed organic matter input of a transitional (terrestrial to marine) environment in the Yaya-Ngari area. This shows a progressive movement towards marine source input. Paleodepositional conditions of organic matters weresuboxic to oxic in Maiganga, while the mixed organic matters in Yaya-Ngari were deposited in suboxic conditions. Based on organic petrology and bitumen extraction data, the Maiganga coal was distinctly observed to be immature of pre–oil generation window, while the Yaya-Ngari is in early oil generation window. These analysed sediments are mainly gas prone based on the dominance of Type III kerogen, although the presence of Type II/III kerogen supported by the PY-GC data and relatively higher HI may indicate gas/oil potential for the Maiganga coal. On the other hand, Type IV kerogen dominated the Yaya-Ngari samples. This suggests that these shales are gas prone or do not possess any hydrocarbon generation potential as indicated by the very low HI values. The ICPMS result indicates predominantly semi-arid paleoclimatic condition and a passive continental margin setting based on the binary plots of SiO2 versus (Al2O3 + K2O + Na2O) and log SiO2 versus (K2O/Na2O) for the Gongola sub-basin (shales and mudstones) samples. This is in accordance with the tectonic events of in the West and Central Africa during the Cretaceous period due to separation of South America plate. The predominating force controlling the separation of the West African plates is opening of the Atlantic Ocean in the Early Cretaceous. This data therefore, could be used as a guide for future exploration campaigns in the coal and coal bearing Formations in the Northern Benue Trough and the world at large.